Controllability of Markovian jump Boolean control networks - Meng, Min (2020)
In this paper, controllability of Markovian jump Boolean control networks (MJBCNs) is studied via semi-tensor product of matrices. First, based on the algebraic expression of the considered Boolean control networks, a necessary and sufficient condition for controllability is presented by iteration equations, which however may lead to high-dimensional matrices. To avoid having such matrices, a new matrix is defined and applied to derive another equivalent condition to verify controllability of MJBCNs. Moreover, a maximum principle of MJBCNs is established to further study the minimal controllable time. Finally, two examples are presented to illustrate the obtained results.